2016
DOI: 10.1111/jzo.12392
|View full text |Cite
|
Sign up to set email alerts
|

Environment‐dependent plasticity and ontogenetic changes in the brain of hatchery‐reared Atlantic salmon

Abstract: Lowered rearing density has repeatedly been shown to increase the performance of hatchery-reared salmonids stocked into natural environments. One possible mechanism for this pattern could be that lower densities enhance brain development, which has been shown to be the case in other hatchery enhancement strategies, like environmental enrichment. Here, we investigated the size of the brain in hatcheryreared Atlantic salmon Salmo salar kept at standard (high) and reduced (low) tank densities. In contrast to our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 52 publications
(73 reference statements)
3
23
0
Order By: Relevance
“…Recent studies have identified an array of factors that may influence the relative size of these regions. For example, under hatchery conditions, high population density in Atlantic salmon (Salmo salar Linnaeus, 1758) results in larger telencephalons and cerebella (Näslund et al 2017), while captive rearing produces larger optic tecta in juvenile coho salmon (Oncorhynchus kisutch (Walbaum, 1792)) (Kotrschal et al 2012). Ninespine sticklebacks (Pungitius pungitius (Linnaeus, 1758)) raised in a social environment have been shown to invest more in their optic tecta and less in olfaction (Gonda et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified an array of factors that may influence the relative size of these regions. For example, under hatchery conditions, high population density in Atlantic salmon (Salmo salar Linnaeus, 1758) results in larger telencephalons and cerebella (Näslund et al 2017), while captive rearing produces larger optic tecta in juvenile coho salmon (Oncorhynchus kisutch (Walbaum, 1792)) (Kotrschal et al 2012). Ninespine sticklebacks (Pungitius pungitius (Linnaeus, 1758)) raised in a social environment have been shown to invest more in their optic tecta and less in olfaction (Gonda et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, this type of study has been conducted using either wild-caught or laboratory (hatchery) strains of prey exposed to some degree of chronic predation (Gonda et al 2011;Handelsman et al 2013;Kotrschal et al 2017). The related laboratory studies have employed long periods of conditioning with levels of perceived risk elevated for one or more months (Gonda et al 2009a(Gonda et al , 2012(Gonda et al , 2013Näslund et al 2017;Reddon et al 2018). In both the wild and the laboratory, subjects exposed to elevated predation for extended periods exhibited distinct brain morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with structural enrichment, group size is less investigated with respect to brain growth, but may still be an important environmental factor (Gonda et al 2009(Gonda et al , 2013Johnsson et al 2014;Fischer et al 2015). A recent study on Atlantic salmon reared at either high or low density showed that the cerebellum and telencephalon, both being brain subregions involved in cognitive ability (Ebbesson and Braithwaite 2012), were found to be larger on average in individuals reared at high density in a Danish salmon hatchery (Näslund et al 2017). High-density fish from the same experiment did, however, have lower survival when released into the wild, speaking against a strong benefit of the environmentally induced effects on the brain (Larsen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While the results suggest that there are no detectable differences in brain size between the sexes in individuals smaller than ≈130 mm, it should be noted that differences in specific brain substructures may still be present without affecting total brain size (see e.g., [30]). The lack of sex differences in total brain size in the smolts is in line with results from Atlantic salmon, where hatchery salmon pre-smolts (160-220 mm) were not showing any sex dependent differences in overall brain mass [46].…”
Section: Emerging Sex Differences Depending On Sex Bias Within Diffementioning
confidence: 68%
“…More specifically, when guppies (Poecilia reticulata Peters, 1859) were selected for larger and smaller than average brain size, the large-brained fish developed guts with relatively lower wet mass and also produced fewer offspring in their first parturition [15]. In fish, relative brain and intestinal size are not only determined by genetic background, but also by environmental factors and somatic growth rate [22][23][24][25][26][27][28][29][30], and could thus be suitable for investigating energy allocation trade-offs over the life of fish.…”
Section: Introductionmentioning
confidence: 99%